Fumarate-Mediated Inhibition of Erythrose Reductase, a Key Enzyme for Erythritol Production by Torula corallina - Lee, Jung-Kul (American Society for Microbiology, 2002)
Torula corallina, a strain presently being used for the industrial production of erythritol, has the highest erythritol yield ever reported for an erythritol-producing microorganism. The increased production of erythritol by Torula corallina with trace elements such as Cu(2+) has been thoroughly reported, but the mechanism by which Cu(2+) increases the production of erythritol has not been studied. This study demonstrated that supplemental Cu(2+) enhanced the production of erythritol, while it significantly decreased the production of a major by-product that accumulates during erythritol fermentation, which was identified as fumarate by instrumental analyses. Erythrose reductase, a key enzyme that converts erythrose to erythritol in T. corallina, was purified to homogeneity by chromatographic methods, including ion-exchange and affinity chromatography. In vitro, purified erythrose reductase was significantly inhibited noncompetitively by increasing the fumarate concentration. In contrast, the enzyme activity remained almost constant regardless of Cu(2+) concentration. This suggests that supplemental Cu(2+) reduced the production of fumarate, a strong inhibitor of erythrose reductase, which led to less inhibition of erythrose reductase and a high yield of erythritol. This is the first report that suggests catabolite repression by a tricarboxylic acid cycle intermediate in T. corallina.